(untitled) (African Human Mobility Review, 2021)
In recognition of the benefits of migration and the challenges associated with its management, many governments and development partners have, in recent years, been discussing how to develop effective frameworks for migration governance at the national, regional and international levels (Mangala, 2017). As a result of the increasing realisation that population mobility can contribute to socio-economic transformation of both migrant sending and receiving areas, migration management was, in 2015, included in the 2030 Agenda for Sustainable Development and the Sustainable Development Goals (SDGs) (OECD/ILO 2018), marking the first time that migration is formally integrated into the global development agenda.